A Phytopharmacological Review on a Medicinal Plant: Cordia africana Lam. - Gashaw Nigussie; Fozia Ibrahim; Sebsib Neway (Journal of Tropical Pharmacy and Chemistry, 2021)
The use of phytoconstituents single or combined with standard medicines has been utilized in cure of different diseases. Many plants of genus Cordia comprise of trees and shrubs are widely distributed in warmer regions and have been utilized in management of various diseases. Cordia africana Lam. (family- Boraginaceae) is a small to medium-sized evergreen tree, 4 to 15 (30) m high, heavily branched with a spreading, umbrella-shaped or rounded crown. Bole typically curved or crooked. Bark grayish-brown to dark brown, smooth in young trees, but soon becoming rough and longitudinally fissured with age; young branch lets with sparse long. Uses of C. africana: firewood, timber (furniture, beehives, boxes, mortars, church, drums), food (fruit), medicine (bark, roots), fodder (leaves), bee forage, mulch, soil conservation, ornamental, shade. Various phytoconstituents like flavonoids, alkaloids, tannins, terpenoids, saponins, steroids, anthraquinones, carbohydrates and protins having different activities were screened and isolated from different parts of Cordia africana. Various important Pharmacological properties including Antioxidant, Cytotoxicity, anti-inflammatory, anthelmintic, antimicrobial, anti-nociceptive, and others have been well documented for this plant. Therefore, we have briefly reviewed the various bioactivities of Cordia africana to improve our knowledge on plant phytochemicals as therapeutic entities. The present review describes the various phytoconstituents and therapeutic potential of Cordia africana that can be followed for future research on this plant for human health benefits.